Cell wall modifications that alter the exolytic activity of lactococcal phage endolysins have little impact on phage growth - Escobedo, Susana; Pérez de Pipaon, Mikel; Rendueles, Claudia; Rodríguez, Ana; Martínez, Beatriz (Frontiers in Microbiology, 2023)
Bacteriophages are a nuisance in the production of fermented dairy products driven by starter bacteria and strategies to reduce the risk of phage infection are permanently sought. Bearing in mind that the bacterial cell wall plays a pivotal role in host recognition and lysis, our goal was to elucidate to which extent modifications in the cell wall may alter endolysin activity and influence the outcome of phage infection in Lactococcus. Three lactococcal endolysins with distinct catalytic domains (CHAP, amidase and lysozyme) from phages 1358, p2 and c2 respectively, were purified and their exolytic activity was tested against lactococcal mutants either overexpressing or lacking genes involved in the cell envelope stress (CES) response or in modifying peptidoglycan (PG) composition. After recombinant production in E. coli, Lys1358 (CHAP) and LysC2 (muramidase) were able to lyse lactococcal cells in turbidity reduction assays, but no activity of LysP2 was detected. The degree of PG acetylation, namely C6-O-acetylation and de-N-acetylation influenced the exolytic activity, being LysC2 more active against cells depleted of the PG deacetylase PgdA and the O-acetyl transferase OatA. On the contrary, both endolysins showed reduced activity on cells with an induced CES response. By measuring several growth parameters of phage c2 on these lactococcal mutants (lytic score, efficiency of plaquing, plaque size and one-step curves), a direct link between the exolytic activity of its endolysin and phage performance could not be stablished.